(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
This paper proposes a simulation of Photovoltaic energy used to supply an induction motor with acomparison of two types of inverters.In general, the greater number of motorswhich"are used incommercial and industrial applicationsare"induction motors. To use PV source to run the induction motor, an interface circuits are used which are a dc-dc"converter and an inverter, the PV cell has nonlinear behavior,"adc-dc converter is used along with Maximum Power Point Tracker controllerto improve theefficiency by boosting the output voltage of the PV module and to match the load demand."The dc output voltage of PV modulethen"converted to AC, two types of inverter are presented, A conventional Voltage Source Inverter system and multilevel inverter system which employselective harmonic eliminationmethod fed three phase induction motor, these two types of inverters are simulated using Matlab/Simulink and their results are presented. The FFT spectrum is presented of the output currents to analyze the harmonics reduction, which shows that the"multilevel inverter is better than VSI system"according to harmonics reduction and increment in output voltage and power.